"Comparative Glutathione S-Transferases (GSTs) Inhibition Assay in the Whole Extract of Fasciola hepatica and Sheep Liver Tissue by Hexachlorophene" - A Farahnak; J Barrett (Tehran University of Medical Sciences, 2001)
Recent research highlights the importance of GSTs in the establishment of chronic helminth infections. GSTs have the potential to protect the parasite against the host immune response. In this present study, GST enzyme assay has been investigated on whole extract of F. hepatica and sheep liver tissue. To the 1-ml plastic cuvette, added 200 mM potassium phosphate buffer. Then added 50 Mm GSH reduced. Was placed the required volume of F. hepatica or sheep liver extract into the cuvette and mixed well. Added water and equilibrated at room temperature for 5 minutes. Meanwhile was set up the UV spectrophotometer at 340 nm for the GST assay. Finally was placed the cuvette into the barrel of the UV spectrophotometer and added 1-chloro-2, 4-dinitorbenzene (CDNB) and stirred well. For testing an inhibitor of GSTs such as hexachlorophene, mixed the appropriate volume of compound with GSH,reduced buffer, water and protein before equilibrating at room temperature. For calculation of IC50% value a computer package was used. The inhibitor concentration for 50% remaining activity of GSTs calculated graphically and wasobtained 10µl for F. hepatica and 20 µl for liver tissue.